The Public Antagonist and Martyr: Reading A.H.J. Dautzenberg against Literary Typologies - Ven, Inge Van De (Werkwinkel, 2017)
I analyze the public authorship of Dutch writer A.H.J. Dautzenberg. I disentangle some of the main threads in his literature and public persona, singling out three socio-cultural issues on which he has publicly taken a stance in both his literature and his non-fiction texts. I base my analysis on three types of sources: Dautzenberg’s works of literary fiction, appearances in the media, and non-fictional texts. I argue that the case of Dautzenberg brings out the limits of any typology of engaged authorship, autonomous authorship, or stardom, and that his veiled emphasis on factuality under the flag of fiction to an important extent explains the efficiency of his style of media performance, and helps the author generate attention for his work. I conclude that in the final instance, both his work and his media performances are subordinate to his societal engagement, and that therefore, Dautzenberg is a public antagonist first, and an author only secondarily.